Caracterização da zona termicamente afetada de aço produzido via resfriamento acelerado - Ramsés Ferreira da Silva (2010)
Usiminas has been installing in Ipatinga Mill the Accelerated Cooling Technology, which will become able to produce higher tensile steel plates with less carbon equivalent (Pcm), comparatively to carbon steels produced nowadays. This study aimed to characterize and compare a accelerated cooling steel and normalized steel heat affected zone (HAZ), mainly when high heat input welding is used. In order to evaluate specifics HAZ regions, it was simulated welding thermal cycles for both one pass and multiple passes welding employing simulators as a Gleeble and a Dilatometer. Large volume of material with homogeneous microstructure can be produced with these devices. So, it is possible to evaluate the differents HAZ regions when used different heat inputs. It was found that, when was used the same heat input, the accelerated cooling steel showed coarser and higher transformation temperature microstructures. This behavior was associated with lower Pcm of the accelerated cooling steel. It was also observed that for the same heat input, the normalized steel showed massive M-A, located mainly at prior austenite grain boundaries. On the other hand, for the accelerated cooling steel was observed smaller massive M-A located mainly in the inner of the grains. In addition, it was developed a Gleeble welding cycle simulating methodology in order to avoid the problems that happened in this study, like large scatter in Charpy test result and the occurrence, during the simulation, of notch in the jig/sample contact